2007
DOI: 10.1007/s10384-007-0477-7
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Measurements of Cone Photoreceptor Spacing in Myopic Eyes from Images Obtained by an Adaptive Optics Fundus Camera

Abstract: The AO fundus camera is capable of acquiring images of the photoreceptors in normal and myopic eyes. The greater spacing between cones in the myopia group is consistent with histological findings. These results suggest that retinal expansion should be considered in addition to Knapp's law when aniseikonia is evaluated in axial myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Prior AO studies have shown a decrease in cone density in myopic subjects, 22,38 and a similar trend was observed here. The three emmetropic subjects had a mean SE of − 0.25 D, while for the myopes the mean SE was − 3.1 D. Averaging the data from these two groups separately, lower cone and rod densities were found at nearly all retinal locations in the myopic group: 13% lower on average for cones and 19% lower on average for the rods compared to the emmetropic group.…”
Section: Discussionsupporting
confidence: 90%
“…Prior AO studies have shown a decrease in cone density in myopic subjects, 22,38 and a similar trend was observed here. The three emmetropic subjects had a mean SE of − 0.25 D, while for the myopes the mean SE was − 3.1 D. Averaging the data from these two groups separately, lower cone and rod densities were found at nearly all retinal locations in the myopic group: 13% lower on average for cones and 19% lower on average for the rods compared to the emmetropic group.…”
Section: Discussionsupporting
confidence: 90%
“…One reason for reduced vision is spectacle minification resulting in loss of resolution. Other reports have proposed that increased eye length contributing to retinal stretching and spacing of the cone mosaic, morphologic changes in the photoreceptor outer segment, [30][31][32] and decreased subfoveal choroidal thickness delivering less oxygen and nutrients to outer retina may have a role. 33 Also, it was reported that there appeared to be a correlation between degree of myopia at age 14 and subsequent visual loss.…”
Section: Economic Burdenmentioning
confidence: 97%
“…Moreover, it has been described by histological studies that both vessel density and diameter are reduced in the choriocapillaris of highly myopic eyes [8,9]. As the choroid supplies nutrition to retinal pigment epithelial cells and the outer retina, compromised choroidal morphology and circulation may account, in part, for retinal dysfunction and vision loss that is seen in high myopia [10,11]. …”
Section: Introductionmentioning
confidence: 99%